ANALISIS HASIL BELAJAR DAN KEMANDIRIAN SISWA PADA PEMBELAJARAN ASAM BASA DENGAN METODE BLENDED LEARNING (Universitas Negeri Semarang, 2019)
The development of information technology has a big impact on the world of education. Progress in information technology makes it easier to implement learning. Blended learning is one of the learning that is in accordance with these developments.This study aims to analyze the learning outcomes and autonomy of students after blended learning. The research method used is mixed methods. The design used is explanatory sequential design. The research sample was taken using purposive sampling technique, with the study sample using one class in the XI MIPA class of SMA N 1 Padamara. Data collection methods in this study include documentation, tests, observations, questionnaires and interviews. The results of the study showed that the edmodo application assisted blended learning was obtained by the percentage of classical learning completeness of 86.67%, the percentage of skill aspects was 88.40% and the student attitude aspect was 82.29%. The analysis of the autonomy of students in class XI MIPA 1 obtained a percentage of 77.27%. Based on the results of the study, it can be concluded that the learning outcomes and autonomy of students of class XI MIPA 1 in SMA N 1 Padamara on acid-base material with assisted blended learning are edmodo applications are good. This shows that assisted blended learning is an effective edmodo application on student learning outcomes and autonomy.